2018
DOI: 10.1159/000488891
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis Mortality in the United States, 2011–2014

Abstract: Background:The International Classification of Disease, 10th Revision (ICD-10) did not include a code specific for Amyotrophic lateral sclerosis (ALS) until 2017. Instead, code G12.2 included both ALS and other motor neuron diseases (MND). Our objective was to determine US mortality rates for ALS exclusively by excluding other MND and progressive supranuclear palsy. Methods: All mortality data coded as G12.2 under the pre-2017 rubric were obtained for 2011-2014. Deaths without ALS listed in one of the un-coded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
(32 reference statements)
3
21
0
Order By: Relevance
“…The lowest prevalence in the South and West Census regions are most likely related to the population diversity in these states. These findings are also consistent with previous ALS mortality analyses showing that states in more northern latitudes have higher age-adjusted mortality rates than states in southern latitudes (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…The lowest prevalence in the South and West Census regions are most likely related to the population diversity in these states. These findings are also consistent with previous ALS mortality analyses showing that states in more northern latitudes have higher age-adjusted mortality rates than states in southern latitudes (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…Examination of the death certificates showed that 81% (99/122) of the causes of death contained the terms ALS, bulbar ALS, progressive ALS or Lou Gehrig's disease. Non-ALS disorders made-up 13% of the death certificate causes including progressive supranuclear palsy ( n = 13), which is not considered a subtype of MND, 32 , 33 bulgar palsy ( n = 1), progressive muscular atrophy ( n = 1) and primary lateral sclerosis ( n = 1). The remaining seven certificates indicated the nonspecific terms of motor neuron disease, of which two specified familial MND and Kennedy's syndrome MND, which is a hereditary disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Examination of the death certificates showed that 26 of the 30 certificates (87%) indicated ALS as the cause of death and the remaining four stated MND of progressive supranuclear palsy, which is not ALS and is not considered a subtype of MND. 32 , 33 Military service was indicated on one of the thirty death certificates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations